PERANCANGAN ARSITEKTUR MENGGUNAKAN KERANGKA KERJA ZACHMAN UNTUK SISTEM INFORMASI PERUMAHAN DAN PERMUKIMAN (SIPERKIM) - Pamuji, Geraldi C; Singgrit, Pini (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2021)
Enterprise architecture plan of Karawang public housing agency information system designed using Zachman framework and used as reference for planning an enterprise architecture SETTLEMENT AND HOUSING AREA INFORMATION SYSTEM so that able to build an integrated information system to make the good governance comes true, especially in applications. Data collections have been done by Interviews and document analysis. Analysis parameters used are Strenghts, Weakness, Opportunities, threats (SWOT) dan Value Chain. This Enterprise architecture planning intends to build integrated information system from villages to cities through Karawang public housing agency. The result of this research is a blueprint on zachman framework that can be seen from planner and owner perspective with 4 sides, they are Data (what), Function (how), Network (where), and people (who), so that it can support application process in Karawang public housing agency.